Canadian Music Studies and/under the Second Trump Presidency - Elliott, Robin (Intersections, 2022)
This talk explores the evolving landscape of Canadian music studies in the context of intensifying cross-border cultural and political pressures. Drawing upon historical reflections and contemporary developments, the presentation examines how Canadian music scholarship navigates questions of national identity, academic autonomy, and cultural preservation. It considers the influence of dominant U.S.-based institutions and academic societies on Canadian music studies and reflects on the challenges posed by shifting geopolitical dynamics, including threats to Canadian sovereignty and academic freedom. The talk highlights the resilience and diversity of Canadian musical traditions and underscores the importance of sustaining a distinct Canadian musical identity. Through case studies, historical parallels, and current responses from artists and scholars, the talk invites a broader conversation about the role music studies might play in affirming cultural sovereignty and fostering inclusive, forward-looking scholarship.